New directions in the conceptualisation of athlete burnout - Isoard-Gautheur, S.; Guillet-Descas, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Athlete burnout (AB) has been a growing subject of interest during the past decade. Raedeke and Smith (2009) developed a multidimensional definition based on the workplace definition, and characterized AB as a syndrome with three key dimensions: (a) reduced sense of accomplishment, which correspond to a sense of ineffectiveness and a tendency of an individual to evaluate himself negatively in terms of performance and athletic achievements, (b) sport devaluation, which corresponds to a negative and detached attitude towards sport, resulting in a lack of interest about sport and performance, and (c) emotional and physical exhaustion, which refers to a feeling of emotional and physical fatigue stemming from the high demands associated with trainings and competitions. AB is considered as a syndrome with three dimensions that means that in order to consider that an athlete is burned out, he might report moderate to high scores on all the three dimensions (Eklund & Cresswell, 2007). Recent qualitative studies using retrospective interviews have proposed that the three dimensions of AB develop among time and that sport devaluation might be the last step of a sequence involving emotional/physical exhaustion and reduced sense of accomplishment (Cresswell & Eklund, 2007; Gustafsson, Hassmèn, Kenttä & Johansson, 2008). Otherwise, Lonsdale, Hodge and Jackson (2007) have suggested to reconsider the emotional and physical exhaustion dimension of AB. In line with the items in the Athlete Burnout Questionnaire (ABQ; Raedeke & Smith, 2009) it can be supposed that the two aspects of exhaustion can be two separate dimensions of AB. The first aim of the present study was to examine the prevalence of AB and its developmental sequence. The second aim was to develop a revised version of the ABQ (ABQ-R) by splitting exhaustion in two dimensions. Methods: Adolescents involved in elite training centres have participated in two studies aimed to test the hypothesis. Growth curve and cluster analyses were used to examine the prevalence and the developmental sequence of AB. Expected Results and Discussion: A developmental sequence involving the three dimensions of AB should be found. Specifically, we assume that sport devaluation should be the last step of the developmental sequence. Moreover, we expect that the ABQ-R offer good properties and could be used to reveal different profiles of AB among adolescents in elite training centres.